Speaking Anxiety in Chinese Language Learning Among non-Chinese Learners in Malaysia 马来西亚非华裔生汉语口语焦虑调查 - TING Hie Ling; CHONG Pei Qi; LAM Kai Chee; Sunarti Sunarti (Sinolingua: Journal of Chinese Studies, 2023)
Numerous studies indicate most of the foreign language learners experience certain level of anxiety and usually they experience anxiety in their speaking skills. Hence, this study examines the speaking anxiety in Chinese Language learning among non-Chinese Beginner learners from University Teknologi MARA (Sarawak). The questionnaire which was developed by Horwitz, Horwitz and Cope (1986) was used in this study. SPSS 25.0 was used to analyze the scores. The result revealed non-Chinese beginner learners experienced speaking anxiety in Chinese language learning. Majority of them experience a moderate level of speaking anxiety in Chinese language learning. The main factor that contributed to non-Chinese beginner learners’ speaking anxiety was communication apprehension. It was followed by test anxiety and fear of negative evaluation.